Immunity to non-cerebral severe malaria is acquired after one or two infections. - Gupta, S; Snow, R; Donnelly, C; Marsh, K; Newbold, C (1999)
In areas of stable transmission, clinical immunity to mild malaria is acquired slowly, so it is not usually effective until early adolescence. Life-threatening disease is, however, restricted to a much younger age group, indicating that resistance to the severe clinical consequences of infection is acquired more quickly. Understanding how rapidly immunity develops to severe malaria is essential, as severe malaria should be the primary target of intervention strategies, and predicting the result of interventions that reduce host exposure will require consideration of these dynamics. Severe disease in childhood is less frequent in areas where transmission is the greatest. One explanation for this is that infants experience increased exposure to infection while they are protected from disease, possibly by maternal antibody. They therefore emerge from this period of clinical protection with considerably more immunity than those who experience lower transmission intensities. Here we use this data, assuming a period of clinical protection, to estimate the number of prior infections needed to reduce the risk of severe disease to negligible levels. Contrary to expectations, one or two successful infective bites seem to be all that is necessary across a broad range of transmission intensities.